Olakunle Osundina and his Paintings - Sobowale, Tolulope Oladimeji; Umoru-Oke, Nanashaitu A.; Olojo-Kosoko, Kolawole K.; Oni, Akinsoji F.; Oshinsada, Olusoji O. (NIU Journal of Humanities; Vol 9 No 2 (2024): NIU Journal of Humanities, Vol. 9 No. 2, June 2024, 2024)
This study examines selected works of Olakunle Osundina (1971-2018), a contemporary Nigerian artist, and his contributions to Nigerian art. It highlights the underlying Yoruba philosophical expressions encoded in the works of Olakunle. The study relied more on the fieldwork carried out between May 2016 and January 2017 where several studio visits were made to his studio in Akute, Ogun State. Oral interviews were conducted with Olakunle where first-hand information was gathered about his artistic development, studio practice and philosophy. Photographs of some of his works were taken, examined and analysed to bring out his socio-cultural inclination. The study adopted Stuart Hall's concepts of representation to analyse the themes of selected works. It is concluded that Olakununle was not just an artist who was merely interested in the visual representation of events around him, but one with a solid root of his socio-cultural and ethnic background and this is evident in his works, which represent Yoruba philosophical teachings and learnings. Keywords: Yoruba, visual art, idiomatic expression, Olakunle Osundina, and Onaism.